Anatomical and physico-chemical alterations associated with cold storage of ’Aurora-1’ and ’Dourado-2’ peaches - Bron, Ilana Urbano; Jacomino, Angelo Pedro; da-Glória, Beatriz Appezzato (Pesquisa Agropecuaria Brasileira, 2002)
The objective of the present study was to evaluate the anatomical and physico-chemical characteristics of 'Aurora-1' and 'Dourado-2' peaches (Prunus persica (L.) Batsch) stored at different temperatures and periods. In the first experiment, fruits were stored at 0, 3 and 6ºC for 14, 21, 28 and 35 days (more two days of simulated commercialization period at 25ºC). In the second experiment, fruits were stored at 0 and 3ºC for 7, 14, 21, 28 and 35 days (more two days at 25ºC of simulated commercialization period). The experiment was a factorial with a completely randomized design with four replicates with six fruit parcels. 'Dourado-2' peaches after seven days of storage at 3ºC or 14 days of storage at 0ºC showed woolliness characterized by a sharp decrease in firmness and low juice content. The mesocarp symptoms were characterized by a separation of cell walls, pectin accumulation into the cells and intercellular spaces. 'Aurora-1' peaches lost firmness without compromising fruit quality; they could be conserved for up to 35 days at 0 or 3ºC; even at 35 days of storage, mesocarp did not present typical alterations of woolliness. At 35 days of storage at 6ºC, the fruits of both cultivars were overripe.